Modern assets in security screening and counter terrorism - Kojadinović, Predrag M. (Vojnotehnički glasnik / Military Technical Courier, 2019)
The article first briefly discusses hazardous materials, namely their concept and classification. One part of the article is focused on the detection of hazardous materials and the detection of fuzes and initial components of explosive devices. In addition, it presents some of modern counter-terrorist and security screening devices used in Serbia as well as in foreign countries, based on the data collected during a visit to the counter terrorist units of the Serbian Army and the Ministry of Interior of the Republic of Serbia. The aim of the paper is to contribute to gaining an insight into the acquired knowledge of security and protection equipment, detection devices and  hazardous materials in particular. The knowledge gained by analyzing and comparing available literature and previous research is expected to lead to raising awareness of the importance of usage of modern equipment which must keep pace with means used by terrorists and commandos in their attacks.
Keywords: counter- diversion protection; hazardous materials; detection of hazardous materials; detection of fuzes - inital components of explosive devices; detection devices